English: Bahasa Indonesia - Fauzan Juliansyah; Diki Rukmana (Universitas Majalengka, 2022)
Based on the identification of the problem, many Indonesian people, especially school children, are still not interested in reading activities. One of the efforts to increase interest in reading promoted by the government is to promote a reading corner program in schools. This study aims to determine the effect of the reading corner program in terms of the quality of the reading corner and the teacher's role in using the reading corner to increase the reading interest of fourth grade elementary school students in the Cijantung-East Jakarta area. By using survey research methods, the research instrument consists of 23 Questionnaire statement items were distributed to 4 schools consisting of 2 public elementary schools and 2 private elementary schools with a total sample of 233 students. Confirmatory Factor Analysis and Structural Equation Modeling (SEM) were performed to analyze instrument validation and test hypotheses. The results of the factor analysis showed that of the 23 instruments tested, there were 6 items that did not meet the requirements because they had an unqualified loading factor so that only 16 statements were used for analysis. The results of the SEM analysis show that the increase in reading interest is not dominantly influenced by the quality of the reading corner itself, but must be accompanied by the role of the teacher. These results indicate that the implementation of the reading corner program in schools is not only physically present but also must be supported by the role of the teacher.